I, too, am America - Hughes, Langston, 1902-1967 (Simon & Schuster Books for Young Readers, 2012)
Presents the popular poem by one of the central figures in the Harlem Renaissance, highlighting the courage and dignity of the African American Pullman porters in the early twentieth century.